Mahasiswa Rantau Fakultas Psikologi Universitas Semarang : antara Persepsi Pola Asuh dan Regulasi Emosi - Ardiansyah, Dicky Syahrul; Winta, Mulya Virgonita Iswindari; Nusandhani, Arumwardani (Reswara Journal of Psychology, 2023)
This study aims to empirically examine the relationship between parenting perception and emotional regulation in regional students of the Faculty of Psychology class of 2020, Semarang University. In this study, the hypothesis is that there is a positive relationship between the relationship between parenting perception and emotional regulation in regional students of the Faculty of Psychology, class of 2020, Semarang University. The more positive the perception of parenting in regional students, the higher the emotional regulation in regional students. This research involved regional students of the Faculty of Psychology class of 2020 as research subjects. The data analysis used in this study used the Product Moment Correlation Technique. This research data was collected using two scales, namely the emotion regulation scale and the parenting perception scale. Data analysis was carried out using the person correlation test obtained using the SPSS (Statistical Package for Social Science) program version 20. The results showed that there was a significant relationship between parenting and emotional regulation in regional students of the Faculty of Psychology batch 20. With a correlation person = 0.001 with a correlation value of 0.336. Thus, the hypothesis in this study is accepted.